Mengembangkan Gerak Tari Berbasis Dolanan Anak sebagai Media Pembelajaran Kreatif - Aulia, Rahma Dwi; Hartono Hartono (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
This study aims to develop dance movements based on traditional children's games (dolanan anak) as a creative learning medium in elementary schools. Dolanan anak is a cultural heritage rich in educational values that can be integrated into dance learning to enhance students' creativity. The research method used is Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research subjects were students in grades III and IV at SDN 05 Ngaglik, totaling 32 students. The instruments used included observation sheets, questionnaires, and movement creativity assessment rubrics. The results showed that the dance movement model based on dolanan anak received an expert validation score of 87.5% (highly feasible), student response reached 89.2% (very good), and there was a 34.7% increase in student creativity from the initial to the final condition. Based on these results, it can be concluded that the development of dance movements based on dolanan anak is proven effective as a fun and meaningful creative learning medium for students.